Pengaruh Job Complexity, Job Knowledge dan Job Experience dengan Self-Efficacy Sebagai Variabel Moderasi Terhadap Audit Judgment - Ahmad Luqmanul Hakim; Saiful Anwar (Universitas Indo Global Mandiri)
The purpose of this research is to test the influence of job complexity against audit judgment; job knowledge against audit judgment; job experience against audit judgment and self-efficacy moderating job complexity, job knowledge also job experience against audit judgment. In this study using several related theories, namely theory of planned behaviour, social cognitive theory and also attribution theory. The method used in this research is quantitative method by using primary data obtained by spreading questionnaire and measured using likert scale. The object of this research is auditors at public accounting firms in East Surabaya. This study uses proportional random sampling techniques. The sample used in this study was 100 respondents. The analytical technique used in this study was Partial Least Square (PLS) using WarpPLS 6.0. the results of this research are interpreting that job complexity has not influences against audit judgment; job knowledge has a positive and significant influences against audit judgment; job experience has a positive and significant influences against audit judgment; self-efficacy has a moderating influence with negative and significant effect of job complexity, job knowledge and job experience against audit judgment.Keywords: Job Complexity, Job Knowledge, Job Experience, Self-Efficacy, Audit Judgment